J’ai un accent, moi ? Les médias et les caractéristiques « atypiques » des personnalités politiques - Philippe Chassé; Alizée Pillod (Glottopol, 2023)
This study aims to provide a more detailed account of how the media cover the appointment to political office of individuals with characteristics that can be deemed “atypical” because of their under-representation in politics. More precisely, it focuses on the media coverage of political figures with non-standard accents, and is based on a case study, namely the appointment of Jean Castex as Prime Minister of France. The results of the content analysis conducted by the authors highlight the fact that even if accents are unrelated to a person’s ability to serve as Prime Minister, journalists do give them importance. They also show that accents are not necessarily presented in a neutral fashion, and that the use of negative qualifiers is common. Finally, results reveal that accents are often used to create a narrative around newly appointed individuals.